2019
DOI: 10.1111/iej.13201
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of immature teeth with nonvital pulps in adults: a prospective comparative clinical study comparingMTAwith Ca(OH)2

Abstract: Aim To evaluate and compare the influence of various predictors on outcomes of apexification using either mineral trioxide aggregate (MTA) or calcium hydroxide (CH) in permanent immature anterior teeth with necrotic pulps and periapical lesions of adults. Methodology Ninety immature teeth with necrotic pulps and periapical lesions on adult patients (aged 18–40 years) were treated with MTA (45 teeth) or CH (45 teeth) between 2015 and 2018. Patients of both groups were recalled for follow‐up examinations after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
(229 reference statements)
0
11
0
1
Order By: Relevance
“…In the MTA study group, three of the included studies reported similar time of medication—i.e. one to four weeks—with the exception of a prolonged time frame in one of the control groups where the final treatment was postponed until a complete apical calcific barrier was observed radiographically and confirmed clinically (Kandemir Demirci et al 2019 ). Two of the MTA studies did not provide data about the total medication time (Demiriz and Hazar 2017 ; Mente et al 2013 ).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In the MTA study group, three of the included studies reported similar time of medication—i.e. one to four weeks—with the exception of a prolonged time frame in one of the control groups where the final treatment was postponed until a complete apical calcific barrier was observed radiographically and confirmed clinically (Kandemir Demirci et al 2019 ). Two of the MTA studies did not provide data about the total medication time (Demiriz and Hazar 2017 ; Mente et al 2013 ).…”
Section: Resultsmentioning
confidence: 96%
“…The results showed that the included studies in both groups were heterogeneous regarding the outcome measurements. Only three studies reported Cvek’s stage of root development at baseline—one study in the RET group (Chan et al 2017 ) and two studies in the MTA group (Kandemir Demirci et al 2019 ; Bucher et al 2016 ). Based on the comparison of the mean age values between the two study groups, we assumed that RET studies included teeth with a lower stage of root development than the MTA studies (mean age RET 8.33 years; mean age MTA 18.39 years) (Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations